Apropriação do espaço público urbano pelo comerciante informal na Avenida Expedito Garcia, Campo Grande, Cariacica-ES - Marques, Ivana Souza (2010)
As a strong image presented in the city scenario, the trader is also an essential character to the whole comprehension of how the city is formed and one of the keys to the evolution and consolidation of the urban centers as well. This paper develops itsel